Conflict probability estimation between aircraft with dynamic importance splitting - Jacquemart, Damien; Morio, Jérôme (Safety science, 2013)
► Aircraft path modelled with realistic Markov chains based on measured trajectory database. ► The proposed scenario estimates collision and conflict probabilities for given flight plans. ► Improved estimation with splitting algorithm instead of Monte Carlo simulations. In this article, conflict probability between aircraft in uncontrolled airspace is estimated. For that purpose, one reviews how to characterize aircraft trajectories with stochastic processes. Indeed, Markov chain model enables us to simulate aircraft trajectories. Conflict probabilities can be estimated with Monte Carlo simulations. Nevertheless, since Monte Carlo methods are not efficient to estimate small probabilities, one proposes the use of the important splitting method. This algorithm is applied on realistic situations of aircraft conflict.